A GPS tracking study of recreationists in an Alaskan protected area. (April 2018) - Stamberger, Lorraine; van Riper, Carena J.; Keller, Rose; Brownlee, Matthew; Rose, Jeff
Abstract: Understanding human movement and behavior in parks and protected areas is an integral part of managing social-ecological systems. In particular, spatial travel patterns of recreationists and their impacts on ecosystems have been studied in many protected area contexts. However, there is limited knowledge of recreation behavior in areas with little to no infrastructure or without formal trail systems. Drawing from Global Positioning System (GPS) tracking data, we identified travel patterns of recreationists in a nearly trail-less backcountry setting in Alaska. Specifically, we investigated the spatial and temporal dynamics of recreation use in relation to resource conditions experienced in Denali National Park and Preserve during the high-use season of 2016. We observed that recreationists' travel routes were heavily concentrated along the Denali Park Road and exhibited different spatial patterns for day and overnight backcountry use. Also, informal campsite locations, delineated using multi-day GPS tracking data, showed uneven distributions within the park. This study provides recommendations for public land management agencies in the US and highlights the need for more systematic evaluations of concentrated use in parks and protected areas. Highlights: Spatial and temporal data derived from GPS units were recorded for multi-day trips. Routes and access points were concentrated despite Denali's trail-less status. GPS tracking data showed overnight backcountry use was more dispersed than day use. High and low priority locations were identified using social and ecological data. Viewshed and land-cover were analyzed in relation to informal campsite locations.